2014
DOI: 10.1016/j.jpedsurg.2014.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal alkaline phosphatase is protective to the preterm rat pup intestine

Abstract: Background Necrotizing enterocolitis (NEC) is the most common surgical emergency in neonates, with a mortality rate between 10 and 50%. The onset of necrotizing enterocolitis is highly variable and associated with numerous risk factors. Prior research has shown enteral supplementation with intestinal alkaline phosphatase (IAP) decreases the severity of NEC. The aim of this study is to investigate whether IAP is protective to the preterm intestine in the presence of formula feeding and in the absence of NEC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Importantly, oral ALPI supplementation protected ALPI-deficient mice from increased susceptibility to DSS-induced colitis (Ramasamy et al, 2011) and from chronic colitis induced by recurrent non-lethal infections by S. typhimurium (Yang et al, 2017). This treatment also significantly reduced intestinal inflammation in several mouse models of colitis and prevented LPS translocation (Ramasamy et al, 2011;Martínez-Moya et al, 2012;Rentea et al, 2012;Heinzerling et al, 2014;Biesterveld et al, 2015). Moreover, a small trial in patients with ulcerative colitis showed that administration of exogenous ALPI was not only well tolerated but also associated with short-term improvement in clinical scores (Lukas et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, oral ALPI supplementation protected ALPI-deficient mice from increased susceptibility to DSS-induced colitis (Ramasamy et al, 2011) and from chronic colitis induced by recurrent non-lethal infections by S. typhimurium (Yang et al, 2017). This treatment also significantly reduced intestinal inflammation in several mouse models of colitis and prevented LPS translocation (Ramasamy et al, 2011;Martínez-Moya et al, 2012;Rentea et al, 2012;Heinzerling et al, 2014;Biesterveld et al, 2015). Moreover, a small trial in patients with ulcerative colitis showed that administration of exogenous ALPI was not only well tolerated but also associated with short-term improvement in clinical scores (Lukas et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Rather, infants born at moderate-and late-preterm gestations represent 85% preterm population 23 and thus pose the greatest potential public health burden of adult morbidity consequent on preterm birth. 5,24 Compared to other paradigms of preterm birth in small animals, 17,22,25 we believe that our medical induction of labour confers significant theoretical and survival advantages. First, the combination of progesterone blockade followed by stimulation of uterine activity and vaginal delivery more closely emulates the normal parturition process.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal ALP (iALP) is a brush-border-associated protein secreted by enterocytes and its activity is considered a valuable marker of crypt-villus differentiation (Sussman et al 1989;Fevr et al 2007). The exact function of iALP is not known, but recently it has been the focus of studies investigating a protective role against lipopolysaccharide-mediated enterocolitis (Heinzerling et al 2014;Goldberg et al 2008). We did not have sufficient serum sample volume to differentiate the various alkaline phosphatase isozymes.…”
Section: Discussionmentioning
confidence: 99%